Occupational change and the demand for skill, 1940-1990 - Welch, Finis; Murphy, Kevin (American Economic Review, 1993)
In 1940 the average worker in the United States had 9.2 years of schooling; by 1990 the average had increased to 13.3 years. Although education levels show a dramatic upward trend, there is no corresponding long-term trend toward lower economic rewards from schooling. In fact, the return to schooling increased in three of the five postwar decades and is higher in 1990 than it was in 1940.1 In our opinion, the tremendous growth in the supply of more-educated labor with no corresponding reduction in relative wages is evidence that the demand for education increased greatly between 1940 and 1990 (see Murphy and Welch [1992] for a similar argument for the 1970-1989 period). In this paper we examine changes in the occupational wage and employment structure at ten-year intervals from 1940 to 1990 in an attempt to identify and quantify some of this increased demand for skill. Our analysis is based on the five Decennial Census files from 1940 to 1980 and the Current Population Surveys for 1978-1982 and 1989-1991. Not surprisingly, our findings support the view that the demand for skill increased significantly over the 1940-1990 period. Over the full period and for each of the five decades, we find that employment shifted from less-educated and lower-paid occupations toward more-educated and higher-paid occupations. We interpret this shift in employment patterns as evidence of a shift in demand. We do not find that the demand for skill grew particularly rapidly during the 1970's and 1980's, a period when wage inequality expanded in comparison to the three earlier decades when the trend was either toward less wage inequality or when wage inequality increased only modestly.